The Effects of Increasing Stocking Density on Finishing Pig Growth Performance and Carcass Characteristics - L. L. Thomas; R. D. Goodband; M. D. Tokach; J. M. DeRouchey; J. C. Woodworth; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 405 pigs (PIC 327 × 1050) from 2 consecutive finishing groups (group 1 initially 145 ± 3.9 lb, group 2 initially 134 ± 5.5 lb) were used to examine the effects of stocking density on finishing pig growth performance and carcass characteristics. Pigs were randomly allotted to pens upon entry into the finishing facility. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 3 treatments with either 7 or 8 replications per treatment (group 1 and 2, respectively). Pens were stocked with 9 pigs, and adjustable gates provided treatments that allowed for 9, 8, or 7 ft2per pig. All pigs were fed the same diets in 3 phases. There was a two-hole feeder in each pen providing 1.56 in. of feeder space per pig. In both studies, as stocking density decreased, ADG and ADFI increased (linear; P<0.019), but there was no difference in F/G. In group 1, these effects were evident when pigs reached approximately 238 lb; however in group 2, decreases in ADG and ADFI were already observed when pigs averaged 163 lb. As a result, final weight was 8.5 and 11.7 lb lower (linear; P ≤ 0.005) in groups 1 and 2, respectively, when comparing the lowest and highest stocking density treatments. In group 1, there were no differences in carcass characteristics with the exception of an increase in BF (linear; P = 0.051) as stocking density decreased. In group 2, HCW and BF increased (linear; P ≤ 0.007) and carcass yield decreased (linear; P = 0.004) as stocking density decreased. The k-value for each body weight was calculated at each of the three space allocations using the formula reported by Whittemore. When comparing growth performance to a suggested required k-value of 0.0336, performance should have been affected above 267.2, 224.1, and 183.6 lb at 9, 8, and 7 ft2per pig, respectively. In group 1, these pen weights were not reached until after d 42 (239.8 lb), d 28 (206.9 lb), and d 14 (176.7 lb) for the 9, 8, and 7 ft2per pig treatments, respectively. However, even after d 14 negative effects of increased stocking density were observed on ADFI (linear, P<0.08). In group 2, performance should not have been affected until after d 56 (258.9 lb), d 27 (190.5 lb) and d 14 (162.7 lb) for the 9, 8, and 7 sq ft2per pig treatments. Similar to group 1, feed consumption, and consequently ADG, decreased linearly (linear; P ≤ 0.033) after d 14 as stocking density increased, before pigs reached the k-value that should have influenced performance. The data suggest that the accepted k-value of 0.0336 might underestimate the impact of increased stocking density on ADG and ADFI. Overall, this study indicates that increasing stocking density resulted in poorer ADG driven by a reduction in ADFI.
Keywords: finishing pig; space allowance; stocking density